Analisis Sistem Pembukaan Rekening Tabungan Mudharabah di Bank Jabar Banten (BJB) Syariah - Asya Nurbayani Gumilar; Iwan Setiawan; Rahayu Kusumadewi; Nurhaeti (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze the Mudharabah savings account opening system at Bank Jabar Banten (BJB) Syariah from the perspective of sharia compliance, efficient procedures, and readiness for digitalization services. The method used was a qualitative approach through literature review and direct observation during Field Work Practice (PKL) activities at BJB Syariah. Data were obtained through observation, interviews with bank employees, and discussions with customers. The results indicate that the account opening process complies with sharia principles and the provisions of the DSN-MUI fatwa, particularly in terms of contract disclosure and profit-sharing ratio determination. However, several obstacles were identified, such as a lack of customer understanding of the Mudharabah contract, lengthy administrative procedures, and the suboptimal implementation of account opening digitalization. Therefore, increased sharia education for customers, simplification of administrative procedures, and strengthening of digital services are needed to enhance BJB Syariah's efficiency and competitiveness in the modern banking era.